(xy-1)^2+(x+y-z)(x+y-zxy)因式分解
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/01 09:58:22
(xy-1)^2+(x+y-z)(x+y-zxy)因式分解(xy-1)^2+(x+y-z)(x+y-zxy)因式分解(xy-1)^2+(x+y-z)(x+y-zxy)因式分解(xy-1)^2+(x+y
(xy-1)^2+(x+y-z)(x+y-zxy)因式分解
(xy-1)^2+(x+y-z)(x+y-zxy)因式分解
(xy-1)^2+(x+y-z)(x+y-zxy)因式分解
(xy-1)^2+(x+y-z)(x+y-zxy)
=(x^2y^2-2xy+1)+(x+y)^2-z(x+y)-zxy(x+y)+xyz^2
=x^2y^2-2xy+1+x^2+2xy+y^2-z[(x+y)+xy(x+y)]+xyz^2
=(x^2y^2+x^2+y^2+1)-z(x+y+x^2y+xy^2)+xyz^2
=(x^2+1)(y^2+1)-z[x(y^2+1)+y(x^2+1)]+xyz^2
设x^2+1=a,y^2+1=b
则上式=ab-z(bx+ay)+xyz^2
=ab-bxz-ayz+xyz^2
=b(a-xz)-yz(a-xz)
=(b-yz)(a-xz)
=(y^2+1-yz)(x^2+1-xz)
(xy-1)^2+(x+y-z)(x+y-zxy)因式分解
代数 x^-y^/ x^-(y-z)^ 除以 x^+2xy+y^/(x-y)^-z^ 乘 x^+xy-xz/x^-xy
化简(y-x)(z-x)/(x-2y+z)(x+y-2z)+(z-y)(x-y)/(xy-2z)(y+z-2x)+(x-z)(y-z)/(y+z-2x)(x-2y+z)速速回答
x²-y²+5x+3y+4(x+y-2xy)(x+y-z)+(xy-1)²
已知x,y,z∈R,求证:x^2+y^2>=xy+x+y-1
化简x^2-yz/[x^2-(y+z)x+yz]+y^2-zx/[y^2-(z+x)y+zx]+z^2-xy/[z^2-(x+y)z+xy]
若|x-3|+|y+2|+|2z+1|=0,求(xy-yz)(y-x+z)
X-y-z=x+( )=x-( ) 1-x+2xy-y=1-( )
(2X+Z-Y)/(X^2-XY+XZ-YZ)-(Y-Z)/(X^2-XY-XZ+YZ)
1、y-x/x²-y²2、(x-y)(y-z)(z-x)/(z-y)(y-x)(x-z)
(x+y-xy)/(x+y+2xy)=(y+z-2yz)/(y+z+3yz)=(z+x-3zx)/(z+x+4zx),且2/x=3/y=1/z,则xyz=?
已知(x+y-xy)/(x+y+2xy)=(y+z-2yz)/(y+z+3yz)=(z+x-3zx)/(z+x+4zx),且2/x=3/y-1/z,则xyz=?
解方程组:x+y=2 ,xy+z=1
已知XY+X/X+Y+1=2 XZ+2X/X+Z+2=3 (Y+1)(Z+2)/Y+Z+3=4 求X+Y+Z的值已知(XY+X)/(X+Y+1)=2 (XZ+2X)/(X+Z+2)=3 [(Y+1)(Z+2)]/(Y+Z+3)=4 求X+Y+Z的值
化简(2x-y-z/x^2-xy-xz+yz)+(2y-x-z/y^2-xy-yz+xz)+(2x-x-y/z^2-xz-yz+xy)
(x^2+yz)/(x^2+x(y-z)-yz)+(y^2-xz)/(y^2+y(x+z)+zx)+(z^2+yx)/(x^2-z(x-y)-yx)最后一项应为:(z^2-xy)/(z^2+z(y-x)-xy)
24xy^2z^2(x+y+z)-32xyz(z-x-y)^2+8xyz^3(z-x-y)
24xy^2z^2(x+y+z)-32xyz(z-x-y)^2+8xyz^3(z-x-y)